The Role of Transformative Leadership in Applying Global Quality Management in Central University Libraries: A Case Study of the Skikda University Central Library - DAYAH, Salah; SIDHOUM, Khaleda Hanaa (Journal of Human Sciences, 2020)
The objective of this study is to identify the role of transformative leadership in implementing glaobal quality management in central library of skikda University. The study adopted the descriptive analytical method, as well as the questionnaire which was used as a key tool for data collection. The study community consisted of 24 central library staff, from whom a purposive sample of 15 librarians was selected. The study reached a number of results, the most important of which are: The administrative management staff of the central library in Skikda university enjoys some of the transformative leadership dimensions, in addition to a somewhat positive relationship between the dimensions of transformative leadership and the application of global quality management, the study also made some recommendations that serve its objectives.